Implementasi Teknik Sambung Pucuk untuk Meningkatkan Produktivitas dan Keberlanjutan Tanaman Buah Lokal Duku (Lansium domesticum) di Desa Arisan Buntal, Sumatera Selatan - Bambang Sulistyantara; Rosyi Damayanti; Indung Sitti Fatimah; Aditya Aji Pamungkas; Frisma Aulia Ardhana (Institut Pertanian Bogor, 2024)
Arisan Buntal Village is a small village in South Sumatra's Ogan Komering Ilir district. Duku (Lansium domesticum Corr) is a highly valued commodity in Arisan Buntal. The most significant barrier to straw development in Arisan Buntal is a need for high-quality seeds. Duku are traditionally grown; therefore, they take a long time to produce fruit. As a result, more advanced stitching techniques, such as the grafting technique, are required. However, because the youth of Arisan Buntal knew nothing about it and did not practice it, they tended to abandon the attempt down the business. This activity seeks to provide instruction in the Samsung puck technique production to the Arisan Buntal youth, allowing them to get superior duke crops and encouraging the sustainability of duke crops at the activity site. The evaluation of the activities revealed that the training participants improved their knowledge of duku-related commodities and grafting techniques. The post-test findings showed that 100% of the participants were aware of Arisan Buntal Village's potential as a hub for the growth of duku farming and the clamping method for duku crops. Furthermore, as many as 94% of participants had already tried the procedure with the assistance of specialists. Furthermore, the percentage of participants who prefer to apply the grafting method to the front has increased from 76.5% to 91.7%. The observation shows that the success rate of this technique reached 80%.